Data Stream Management Systems for Computational Finance - Chandramouli, Badrish; Ali, Mohamed; Goldstein, Jonathan; Sezgin, Beysim; Raman, Balan S. (IEEE Computer, 2010)
Because financial applications rely on a continual stream of time-sensitive data, any data management system must be able to process complex queries on the fly. Although many organizations turn to custom solutions, data stream management systems can offer the same low-latency processing with the flexibility to handle a range of applications.